VAR ANALYSIS UNLEASHED: THE VOLATILE IMPACT OF NON-PERFORMING FINANCING ON ISLAMIC BANK PROFITABILITY IN INDONESIA - Harry Irawan; Dede Ruslan; Muhammad Fitri Rahmadana (CV. Radja Publika, 2024)
The purpose of this study is to analyse and understand the impact of Non-Performing Financing (NPF) volatility on the profitability of Islamic commercial banks in Indonesia. This study uses the Vector Auto Regressive (VAR) approach. The results show a strong interdependence between NPF and ROA in Islamic banks in Indonesia. Although in the short term NPF has a negative impact on ROA, in the long term NPF has a positive effect. Variance decomposition indicates that these two variables influence each other and their contribution increases over time. These findings are important for the management of Islamic banks to understand how fluctuations in NPF can affect the financial performance of banks and vice versa, and to make effective strategic decisions in risk management and profitability.